SME AND ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY ADOPTION ON SME INDUSTRY IN MALAYSIA - Azian Othman; Muhamad Saufi Che Rusuli; Wan Mohd Nazdrol Wan Mohd Nasir (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This study examines the challenges faced by small and medium enterprises (SMEs) in adopting Artificial Intelligence (AI) technology in Malaysia. Business sectors have actively embraced the usage of Artificial Intelligence (AI). However, the rate of adoption of AI within the SME sectors is low or slow as compared to larger business corporations. This study proposes a conceptual framework that outlines eight (8) factors that could influence the decision of the SMEs sectors to adopt AI technology in their business process, which will give a positive impact on SMEs growth and development. These factors are Top Management Support, Employee Adaptability, Organization Preparedness, Business Operation Support, Competitive Pressure, Partner Support, Perceived Usefulness, and Perceived Ease of Use. The principles for the framework is the Technology Organization Environment (TOE) model integrated with Technology Acceptance Model (TAM). It is hope that this conceptual framework could provide direction for future additional research on this topic.